Transgenic animal model for studying the mechanism of obesity‐associated stress urinary incontinence. (5th October 2016) - Wang, Lin; Lin, Guiting; Lee, Yung‐Chin; Reed‐Maldonado, Amanda B.; Sanford, Melissa T.; Wang, Guifang; Li, Huixi; Banie, Lia; Xin, Zhengcheng; Lue, Tom F.
Abstract : Objective: To study and compare the function and structure of the urethral sphincter in female Zucker lean (ZL) and Zucker fatty (ZF) rats and to assess the viability of ZF fats as a model for female obesity‐associated stress urinary incontinence (SUI). Materials and Methods: Two study arms were created: a ZL arm including 16‐week‐old female ZL rats (ZUC‐Lepr fa 186; n = 12) and a ZF arm including 16‐week‐old female ZF rats (ZUC‐Lepr fa 185; n = 12). I.p. insulin tolerance testing was carried out before functional study. Metabolic cages, conscious cystometry and leak point pressure (LPP) assessments were conducted. Urethral tissues were harvested for immunofluorescence staining to check intramyocellular lipid (IMCL) and sphincter muscle (smooth muscle and striated muscle) composition. Results: The ZF rats had insulin resistance, a greater voiding frequency and lower LPP compared with ZL rats ( P < 0.05), with more IMCL deposition localized in the urethral striated muscle fibres of the ZF rats ( P < 0.05). The thickness of the striated muscle layer and the ratio of striated muscle to smooth muscle were lower in ZF than in ZL rats. Conclusion: Obesity impairs urethral sphincter function via IMCL deposition and leads to atrophy and distortion of urethral striated muscle. The ZF rats could be a consistent and reliable animal model in which to study obesity‐associated SUI.